A novel nanofiltration based membrane bioreactor (NF-MBR) and reverse osmosis (RO) for water reclamation - Tay, Ming Feng (Nanyang Technological University, 2020)
In this study, a novel nanofiltration membrane bioreactor (NF-MBR) was developed and integrated with the reverse osmosis (RO) process for water reclamation. The underlying motivation of using NF-MBR as a pre-treatment to the RO process is to improve the RO feed quality and subsequently increase the RO recovery ratio. The use of a glutaraldehyde (GA) crosslinked layer-by-layer polyelectrolyte low-pressure hollow fiber NF membrane has overcome the inherent issues of low permeate flux and membrane stability in the NF-MBR system. Higher organic removal was observed in the NF-MBR than the ultrafiltration MBR (UF-MBR) due to the extended retention time that allows the enhanced biodegradation of the retained organics in the bioreactor. In the NFMBR system applied in this study, the negative impact arisen from the salt accumulation was alleviated by allowing the passage of monovalent ions, particularly NaCl. The build-up of salts (i.e., Ca, Mg, PO4) is a function of SRT, hydraulic retention time (HRT) and membrane rejection. Despite the accumulation of salts, the NF-MBRs achieved excellent biodegradation efficiency, organic removal (>97%) and ammonia removal (>98%). The improved MBR permeate quality has led to ~3.7 times decrease in the RO fouling rates as compared to the UF-MBR+RO process. Further analysis indicated that the cake layer fouling that caused the cake-enhanced osmotic pressure (CEOP) effect contributed predominantly to the transmembrane pressure (TMP) increase in the NF-MBR. Our study substantiated that the NF-MBR+RO system is a feasible option for high recovery water reclamation by comparing the energy requirement for the NF-MBR+RO and UF-MBR+RO system.